Perlecan, A Multi-Functional, Cell-Instructive, Matrix-Stabilizing Proteoglycan With Roles in Tissue Development Has Relevance to Connective Tissue Repair and Regeneration - Hayes, Anthony J.; Farrugia, Brooke L.; Biose, Ifechukwude J.; Bix, Gregory J.; Melrose, James (Frontiers in Cell and Developmental Biology, 2022)
This review highlights the multifunctional properties of perlecan (HSPG2) and its potential roles in repair biology. Perlecan is ubiquitous, occurring in vascular, cartilaginous, adipose, lymphoreticular, bone and bone marrow stroma and in neural tissues. Perlecan has roles in angiogenesis, tissue development and extracellular matrix stabilization in mature weight bearing and tensional tissues. Perlecan contributes to mechanosensory properties in cartilage through pericellular interactions with fibrillin-1, type IV, V, VI and XI collagen and elastin. Perlecan domain I - FGF, PDGF, VEGF and BMP interactions promote embryonic cellular proliferation, differentiation, and tissue development. Perlecan domain II, an LDLR-like domain interacts with lipids, Wnt and Hedgehog morphogens. Perlecan domain III binds FGF-7 and 18 and has roles in the secretion of perlecan. Perlecan domain IV, an immunoglobulin repeat domain, has cell attachment and matrix stabilizing properties. Perlecan domain V promotes tissue repair through interactions with VEGF, VEGF-R2 and α2β1 integrin. Perlecan domain-V LG1-LG2 and LG3 fragments antagonize these interactions. Perlecan domain V promotes reconstitution of the blood brain barrier damaged by ischemic stroke and is neurogenic and neuroprotective. Perlecan-VEGF-VEGFR2, perlecan-FGF-2 and perlecan-PDGF interactions promote angiogenesis and wound healing. Perlecan domain I, III and V interactions with platelet factor-4 and megakaryocyte and platelet inhibitory receptor promote adhesion of cells to implants and scaffolds in vascular repair. Perlecan localizes acetylcholinesterase in the neuromuscular junction and is of functional significance in neuromuscular control. Perlecan mutation leads to Schwartz-Jampel Syndrome, functional impairment of the biomechanical properties of the intervertebral disc, variable levels of chondroplasia and myotonia. A greater understanding of the functional working of the neuromuscular junction may be insightful in therapeutic approaches in the treatment of neuromuscular disorders. Tissue engineering of salivary glands has been undertaken using bioactive peptides (TWSKV) derived from perlecan domain IV. Perlecan TWSKV peptide induces differentiation of salivary gland cells into self-assembling acini-like structures that express salivary gland biomarkers and secrete α-amylase. Perlecan also promotes chondroprogenitor stem cell maturation and development of pluripotent migratory stem cell lineages, which participate in diarthrodial joint formation, and early cartilage development. Recent studies have also shown that perlecan is prominently expressed during repair of adult human articular cartilage. Perlecan also has roles in endochondral ossification and bone development. Perlecan domain I hydrogels been used in tissue engineering to establish heparin binding growth factor gradients that promote cell migration and cartilage repair. Perlecan domain I collagen I fibril scaffolds have also been used as an FGF-2 delivery system for tissue repair. With the availability of recombinant perlecan domains, the development of other tissue repair strategies should emerge in the near future. Perlecan co-localization with vascular elastin in the intima, acts as a blood shear-flow endothelial sensor that regulates blood volume and pressure and has a similar role to perlecan in canalicular fluid, regulating bone development and remodeling. This complements perlecan’s roles in growth plate cartilage and in endochondral ossification to form the appendicular and axial skeleton. Perlecan is thus a ubiquitous, multifunctional, and pleomorphic molecule of considerable biological importance. A greater understanding of its diverse biological roles and functional repertoires during tissue development, growth and disease will yield valuable insights into how this impressive proteoglycan could be utilized successfully in repair biology.